Impact of tooth loss on the quality of life of patients seen in a Nigerian teaching hospital (2016)
Introduction. Tooth loss (edentulism) is an irreversible oral condition that has been described as a final marker of disease burden for oral health. It can impact the quality of life of an individual as it may affect speech and ability to chew properly. Aim of the study. To assess the effect of tooth loss on the quality of life of the Nigerian population using the Oral Health Impact (OHIP) questionnaire, and to determine factors that influence the severity of tooth loss impact. Material and method. A cross-sectional study was performed among partially edentulous patients at a Nigerian teaching Hospital. The Oral Health Impact (OHIP) questionnaire was used to obtain information from the participants. Data collected through the questionnaire were analysed using SPSS version 17 software. Chi square test was used to assess the correlation between the quantity and location of tooth loss and impact of tooth loss on the quality of life. The level of significance was set at P≤0.05. Result. One hundred and sixty five partially edentulous patients participated in the study. There were 80 (48.5%) males and 85 (51.5%) females. The highest mean impact score was 2.27 and was recorded for the question “Have you found it uncomfortable to eat any food because of your missing teeth”? Of the seven domains of OHIP, the highest mean score (4.2) was recorded for the physical pain domain. There was a statistically significant relationship between the location of missing teeth and the severity of impact on the quality of life of the participants. Conclusion. Missing anterior teeth had significant impact on the quality of life of the patients